ANALISIS EFISIENSI PENGELUARAN PUBLIK TERHADAP PEMBANGUNAN MANUSIA DENGAN METODE STOCHASTIC FRONTIER ANALYSI - Katlea Rizki Nabilah; Dwi Budi Santoso (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The role of the Government in improving the quality of human development isfrom the fiscal capacity provided, one of which is from the per capita APBD. Thehighpercapita APBD anticipates human development expectations. East Java Provincewitharelatively higher per capita APBD than Indonesia's APBN per capita, has aHumanDevelopment Index (HDI) figure below the national average. Therefore, this studyisapublic expenditure of the East Java regional government with education and healthindicesas outputs. On the other hand, data on the Audit Results Report (LHP), the PerformanceAccountability System for Government Agencies (SAKIP), economic growth, andpercapitaincome are used to see the characteristics of an ef icient region. Datafrom38districts/cities of East Java during 2018-2020 were collected to conduct this research.Stochastic Frontier Analysis (SFA) is used to measure the level of ef iciency. Inaddition,ef icient regional characteristics are also measured using cluster analysis and scoring. Theresults of the SFA and cluster analysis show that there are 25 districts/cities withhigh-ef iciency levels that have performed ef iciently for at least 2-3 years. The resultsof thecluster analysis show that regions with high ef iciency have conditions of growthandincreased economic activity, and are orderly in budget management and planning. Ontheother hand, it can be concluded that the main indicators of the highest ef iciencyineducation and health are regions with orderly financial planning and development.